2007
DOI: 10.1021/cg060450o
|View full text |Cite
|
Sign up to set email alerts
|

Growth of CuGaS2 Single Crystals by Chemical Vapor Transport and Characterization

Abstract: Single crystals of CuGaS2 (CGS) compounds were grown by a chemical vapor transport technique in a closed system using iodine as a transporting agent at different growth conditions. The grown crystals exhibit different colors such as yellow, green, and orange depending on the temperature of the growth zone. Single-crystal X-ray diffraction studies confirmed the chalcopyrite structure of the grown crystals. The powder X-ray diffraction showed the presence of the secondary phase in the yellow (Cu2S) and orange (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…It can be seen that the Raman spectrum of CuGaS 2 is dominated by a narrow band around 307 cm −1 , corresponding to A 1 mode which is associated with the breathing mode appearing in I-III-IV 2 ternary chalcogenides [49,50]. In the case of A 1 mode, the S atom is in perpendicular motion to the c-axis while Cu and Ga atoms remain at rest [22,26]. Moreover, it can also found that there exist two Raman peaks at 112 cm −1 and 386 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the Raman spectrum of CuGaS 2 is dominated by a narrow band around 307 cm −1 , corresponding to A 1 mode which is associated with the breathing mode appearing in I-III-IV 2 ternary chalcogenides [49,50]. In the case of A 1 mode, the S atom is in perpendicular motion to the c-axis while Cu and Ga atoms remain at rest [22,26]. Moreover, it can also found that there exist two Raman peaks at 112 cm −1 and 386 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is difficult how to control the stoichiometric composition and phase purity of product. For this reason, a variety of new methods, such as electrodeposition [16,17], X-ray irradiation [18], vacuum thermal evaporation method under thermal gradient [19], metal organic chemical vapor deposition [20], electron beam evaporation [21], chemical vapor transport [22], hot-injection [23,24], thermolysis of dithiocarbamate precursors [14], were developed. And CuGaS 2 with stoichiometric composition and high phase purity was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Single crystals of Cu(Al x In 1 À x )S 2 solid solutions with x ¼0, 0.2, 0.4, 0.5, 0.6, 0.7, and 1.0 were grown by CVT method [15,16] using ICl 3 as a transport agent. Cu(Al x In 1À x )S 2 compounds were prepared from the powdered mixture of elements (Cu: purity 99.995%, Al: purity 99.9995%, In: purity 99.9999%, and S: purity 99.999%) in the stoichiometric proportion by reaction at 850 1C for 3 days in evacuated quartz ampoules.…”
Section: Methodsmentioning
confidence: 99%
“…For a direct allowed transition or direct bandgap such as CuGaSe2 and CuGaS2, n assumes the value of ½ and then the plot of ( h ) 2 versus photon energy (h ) forms a straight line whose intercept with the ( h ) 2 =0 axis yields the value of the energy bandgap (Eg) [19,20]. films with respect to CuGaSe2 films is evident.…”
Section: Optical Analysismentioning
confidence: 99%